Adult diffuse hepatic hemangiomatosis lesion occupying the entire abdominal and pelvic cavities: a case report - Ge, Ya-Nan; Shao, Yan; Dong, Shu-Chen; Ma, Xing-Bin; Wang, Wei (Frontiers in Medicine, 2024)
Introduction Adult diffuse hepatic hemangiomatosis (DHH) is an extremely rare disease. Consequently, its characteristics are poorly understood. Herein, we report a case of adult DHH involving both liver lobes but without extrahepatic involvement. To the best of our knowledge, this the largest reported adult DHH to date. Case presentation A 51-year-old man was admitted due to abdominal distension and dyspnea. Physical examination revealed marked liver enlargement. Color Doppler, plain and contrast-enhanced computed tomography, and contrast-enhanced magnetic resonance imaging revealed a hepatic lesion sized 35.1 × 32.1 × 14.1 cm occupying nearly the entire abdominal and pelvic cavities. Diagnosis was established by liver puncture biopsy. The patient exhibited clinical signs of portal hypertension and hypersplenism, but remains free of serious DHH-related complications. He is followed up regularly, with proactive evaluation for future liver transplantation. Conclusion This case will contribute to the current knowledge on the clinical and imaging features of this rare entity.